Ageing and chronic intermittent hypoxia mimicking sleep apnea do not modify local brain tissue stiffness in healthy mice. (July 2017) - Jorba, Ignasi; Menal, Maria José; Torres, Marta; Gozal, David; Piñol-Ripoll, Gerard; Colell, Anna; Montserrat, Josep M.; Navajas, Daniel; Farré, Ramon; Almendros, Isaac
Abstract: Recent evidence suggests that obstructive sleep apnea (OSA) may increase the risk of Alzheimer´s disease (AD), with the latter promoting alterations in brain tissue stiffness, a feature of ageing. Here, we assessed the effects of age and intermittent hypoxia (IH) on brain tissue stiffness in a mouse model of OSA. Two-month-old and 18-month-old mice (N=10 each) were subjected to IH (20% O2 40 s – 6% O2 20 s) for 8 weeks (6 h/day). Corresponding control groups for each age were kept under normoxic conditions in room air (RA). After sacrifice, the brain was excised and 200-micron coronal slices were cut with a vibratome. Local stiffness of the cortex and hippocampus were assessed in brain slices placed in an Atomic Force Microscope. For both brain regions, the Young's modulus (E) in each animal was computed as the average values from 9 force-indentation curves. Cortex E mean (±SE) values were 442±122 Pa (RA) and 455±120 (IH) for young mice and 433±44 (RA) and 405±101 (IH) for old mice. Hippocampal E values were 376±62 (RA) and 474±94 (IH) for young mice and 486±93 (RA) and 521±210 (IH) for old mice. For both cortex and hippocampus, 2-way ANOVA indicated no statistically significant effects of age or challenge (IH vs. RA) on E values. Thus, neither chronic IH mimicking OSA nor ageing up to late middle age appear to modify local brain tissue stiffness in otherwise healthy mice.